Formation of the effective environment of business (Путеводитель предпринимателя)
This article shows us author viewing constant and dynamic development as one of the main streams of market economy as a favorable environmentfor different subjects functioning. Entrepreneurship and business owners play important role among factors of social and economic progress in the world.